Effects of the height and interval of cutting on forage production of cunhã (Clitoria ternatea L.) - de Araújo, João Ambrósio; Gadelha, José Adalberto; da Silva, Nilzemary Lima; Pereira, Raymundo Mauro de A. (Pesquisa Agropecuaria Brasileira, 1994)
Cunhã (Clitoria ternatea L.) provides an excellent option for food supplementation for the livestock in the Semiarid Northeast. This research aimed to study the effects of the interval and height of cutting on the forage production of cunhã, and the best combination of those two factors for its rational management. Four cutting intervals were evaluated, that is, 42, 56, 70 and 84 days, and four heights of cutting, 5.0; 10.0; 15.0 and 20.0 cm above the ground level. Total and per cutting dry matter (DM 105°C) production, dry matter percent and crude protein content were measured. A factorial 4 x 4 with a randomized block design and three replications was followed. The height of cutting did not affect (P > 0.05) the total and the per cutting phytomass production, the percent dry matter and the crude protein content of the cunhã. The interval of cutting affected (P < 0.01) the dry matter production per cutting, resulting in an increasing of the production with the length of the interval, up to the 56-day interval. The best combination of interval x height of cutting for cunhã seems to be 56 days and 5.0 cm or 10.0 cm.